Impactos dos círculos de diálogos nas ações socioeducativas desenvolvidas pelo cense de Foz do Iguaçu - Souza, Cristina Silveira Braga de (2022)
The present study is dedicated to the socio-historical construction of Restorative Justice as an action strategy in the socio-educational scope with adolescents in compliance with socio-educational measures of internment at the Socioeducation Center of Foz do Iguaçu-PR, field of research, from the process of their implementation to date. To this end, it analyzes a dialogue circle developed in the institution and discusses how circular practices can contribute to the resocialization of adolescents in conflict with the law. In it, in particular, the theme of the family is addressed, although there is the exact perception that the social production of violence goes beyond the family scope. The research hypothesis chosen is that restoring psychological and emotional ties broken by intrafamily violence is a socioeducational action decisively contributing to the process of overcoming traumatic experiences suffered and carried out in the past, referring to the studies of Howard Zehr and Kay Pranis. The deductive-explanatory method, which made it possible to describe and interpret the practice of circles in CENSE, which favored the logicaldeductive analysis of the action, which demonstrates, through the concreteness of actions and positive experiences, that Restorative Justice can be a path to be followed in the socio-educational context. The analysis also makes it possible to endorse, as a contribution to the State, Public Policies, adolescents and society, that restorative methods and practices, although limited and not without flaws, insofar as they are totally guided by dialogue, effectively contribute to the process of overcoming problems. conflicts, consistent with the social resocializing role of the institution chosen in the research.